Surface Decorating of CH₃NH₃PbBr₃ Nanoparticles with the Chemically Adsorbed Perylenetetracarboxylic Diimide - Zhu, Ruimin (Langmuir : the ACS journal of surfaces and colloids, 2016)
An organic dye-modified organolead halide CH3NH3PbBr3 nanoparticle (cubic) is prepared successfully by using a perylenetetracarboxylic diimide (PDI) bearing an -NH3(+) headgroup as the capping ligand. The nanopartilces are homogeneous with high crystallinity. The photoluminescence of perovskite is quenched completely by the chemically adsorbed PDI molecules. This efficient fluorescence quenching has confirmed that the PDI molecules are anchored on the surface of CH3NH3PbBr3 nanoparticle. The resulting nanoparticles can be dispersed in organic solvents, and the resulting dispersion remains stable for days. This result provides a general guideline for surface engineering of organolead halide CH3NH3PbBr3 nanoparticles